2023
DOI: 10.1002/adom.202201810
|View full text |Cite
|
Sign up to set email alerts
|

Unique 2D Face Topologies in Naphthyl‐Appended Naphtho[k]fluoranthene‐Based 3D Crystals for Optical Waveguide

Abstract: Molecular crystals exhibiting optical waveguiding are strongly dependent on total internal reflection, molecular stacking arrangements, spatial distributions of transition dipole moments, and topologies. Fluoranthene derivatives are popular fluorescent dyes that have not yet been engineered into crystalline optical materials. Here, a naphthyl‐appended naphtho[k]fluoranthene that exhibits efficient fluorescence in solution and in the solid state is newly synthesized through a one‐pot Pd‐catalyzed reaction of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Such a cocrystal is expected to have anisotropic OWG properties. [26,28,29] Microscopic observations and PL spectral measurements of the cocrystal were performed using a focused laser beam (λ ex = 405 nm) as an excitation source (Figure S11). When a 2Dplatelet-shaped cocrystal was irradiated by the focused laser beam, we observed that light was guided toward the edge of the crystal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a cocrystal is expected to have anisotropic OWG properties. [26,28,29] Microscopic observations and PL spectral measurements of the cocrystal were performed using a focused laser beam (λ ex = 405 nm) as an excitation source (Figure S11). When a 2Dplatelet-shaped cocrystal was irradiated by the focused laser beam, we observed that light was guided toward the edge of the crystal.…”
Section: Resultsmentioning
confidence: 99%
“…A large difference in the loss coefficient indicated extremely anisotropic OWG properties. Notably, the anisotropic waveguiding ability and α S /α L values of a 2D platelet crystalbased anisotropic waveguide have been reported to be < 3.9; [26][27][28][29] thus, this cocrystal with a 1D-ordered supramolecular of alternating copolymer was more than an order of magnitude greater, at 41. A 1D copolymer of a highly fluorescent molecule 1 with 2 formed an angle-controlled supramolecular synthons aligned horizontally with the 2D crystal surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic molecular crystals are generally brittle; thus, crystal photonic components, such as optical waveguides (OWGs), resonators, and lasers, have been widely developed as rigid materials. However, organic molecular crystals with mechanical flexibility based on elasticity or plasticity have recently emerged and are gaining interest as irreplaceable OWG platforms. For practical applications, heterostructures composed of organic microcrystals are constructed, and optical logic gates have been demonstrated. Highly aligned organic molecular crystals have been also constructed, even in solution. Among the various organic molecular crystals, those with a needlelike morphology are ideal candidates to transport photons unidirectionally. In organic π-conjugated molecules, exciton–polaritons (EPs) can be formed as a result of strong coupling between excitons and resonator photons. Because of the large exciton binding energies for organic molecules, EPs are formed, even at room temperature.…”
mentioning
confidence: 99%